PENGARUH PENGGUNAAN MEDIA DITIGAL QREATIF EDUCATIVE TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS I SDN ALASRAJAH 02 - Sofiatul Adawiyah Fatha; Mauidatul Hasanah; Ika Dian Rahmawati (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Beginning reading ability is an important basic skill for elementary school students because it serves as a foundation for understanding further learning. However, some students still experience difficulties in recognizing letters, reading syllables, words, and simple sentences. This study aims to determine the effect of using Digital Qreatif Educative media on the beginning reading ability of first-grade students at SDN Alasrajah 02. This study used a quantitative approach with a pre-experimental method and a one-group pretest-posttest design. The research subjects consisted of 25 students. Data collection techniques were carried out through beginning reading ability tests in the form of pretests and posttests. The research instrument was tested for validity and reliability before being used. The data were analyzed using descriptive analysis, normality testing, and mean difference testing. The results showed that there was an improvement in students' beginning reading ability after using Digital Qreatif Educative media. The average score before treatment was 57.40, increasing to 78.20 after treatment. The test results showed a significant difference between the results before and after the use of the media. Therefore, Digital Qreatif Educative media can be used as an interesting and interactive learning medium to improve elementary school students' beginning reading ability